Ready, Set, Reset: Stimulus-Locked Periodicity in Behavioral Performance Demonstrates the Consequences of Cross-Sensory Phase Reset - Fiebelkorn, Ian C. (Society for Neuroscience, 2011)
The simultaneous presentation of a stimulus in one sensory modality often enhances target detection in another sensory modality, but the neural mechanisms that govern these effects are still under investigation. Here, we test a hypothesis proposed in the neurophysiological literature: that auditory facilitation of visual-target detection operates through cross-sensory phase reset of ongoing neural oscillations (Lakatos et al., 2009). To date, measurement limitations have prevented this potentially powerful neural mechanism from being directly linked with its predicted behavioral consequences. The present experiment uses a psychophysical approach in humans to demonstrate, for the first time, stimulus-locked periodicity in visual-target detection, following a temporally informative sound. Our data further demonstrate that periodicity in behavioral performance is strongly influenced by the probability of audiovisual co-occurrence. We argue that fluctuations in visual-target detection result from cross-sensory phase reset, both at the moment it occurs and persisting for seconds thereafter. The precise frequency at which this periodicity operates remains to be determined through a method that allows for a higher sampling rate.